Como um rio que corre para o mar: a força mobilizadora do arcebispo Dom José Maria Pires na Paraíba (1966-1995) - Alves, Naiara Ferraz Bandeira (2023)
Thesis that aims to analyse aspects of the administration of the Archbishop of Paraíba, Dom José Maria Pires, religious who commanded the church in Paraíba between 1966 and 1995, from the perspective that his political-administrative performance of the Catholic Church in Paraíba was configured as an act of mobilizing force in pedagogical, social and, at the same time, religious terms. From his life story and his written records throughout his episcopal activity, theological and political actions, the thesis is developed that Bishop Dom José Maria Pires managed to expand his religious strength (as a bishop) by mobilizing people (mass) to promote actions (movement/acceleration) linked to Liberation Theology. In the theoretical-methodological path followed, the paradox experienced by the Bishop is identified, namely: that of being a religious bureaucrat and, at the same time, a mobilizer around Liberation Theology. The study is divided into four chapters: in the first chapter "Mobilizing clerics and faithful around a project: Theology of Liberation in Paraíba", one can understand Dom José's actions to carry out this project, passing through the speeches and pastoral visits carried out by the bishop and demonstrating how he was a personage watched by the Military Government of Brazil. In the second chapter, “Trajectories and barriers in the role of lay people in the administration and in the discourse of Dom José Maria Pires”, the role and outcome of the Basic Ecclesiastical Communities (CEBs) are outlined, as well as the theological barrier present in the discourses of the Bishop with regard to women. I n the third chapter, “Negro por Mercê de Deus”, the speeches of Archbishop Dom José, published in newspapers of the time, in handwritten documents and in books, on black theology and the praxis of the “Missa dos Quilombos” are analyzed. In the fourth chapter, “The being: Dom José Maria Pires”, there are not only analyzes of the bishop's act of smiling, but also the composition of his being and his actions, in the process of a liberating evangelization, and in the way the media observed him , but also his choice to make references to the Gospel of Saint Matthew.With the contribution of theorists such as BOURDIEU (1989), Weber (2016), Comblin (1977), Boff (1982), Löwy (2016), Coutinho (2012), Torres-Londonõ (2013), a historical narrative is developed and the analysis of a phenomenon, considering, episodically, the actions and reactions of the practitioners of the Western Christian religion, with the possibility of not only seeing beyond the other and their practices, but also considering the look of another being, through a research qualitative bibliographic and documentary source.